ANALISIS TEKNIS DAN EVALUASI KELAYAKAN PEMBANGUNAN JALAN PENGHUBUNG KABUPATEN KAUR-PROVINSI BENGKULU RUAS JALAN TANJUNG KEMUNING - Syahrul Syahrul; Hari Nugraha Nurjaman; Fitri Suryani (Inersia: Jurnal Teknik Sipil, 2019)
The purpose of this study was to evaluate the feasibility of the construction of feeder roads Kaur District-Bengkulu Province street section Tanjung Kemuning. Methods of data collection using the method of observation and documentation. Methods of data analysis using cost analysis which includes the costs of the project, saving the BOK (Vehicle Operation Costs), and travel time savings and economic feasibility analysis includes economic analysis and sensitivity analysis. The results showed that (1) the results of the technical analysis of road pavement structure includes (a) the type of road pavement construction consists of four (4) arrangement of layers, namely 1) the surface layer, thick 10 cm, layer forming material Crescent, 2) the base layer, thick 21 cm, broken gravel layer forming material which doused with liquid asphalt, 3)sub-base layer, thick 23 cm, layer-forming material mixtures of local soil with lime or portland cement, and 4) basic soil layer, thick 41 cm, layer-forming material local soil at the site of road construction projects are compacted; (b) the condition of the pavement include 1) the traffic planning and traffic growth rates, namely a) average growth rate of 4.5%, b) current peak hours is 48 SMP/day, c) LHR value, ie LHR at the beginning of the plan year is 1.200 SMP/day, d) value of LHRT, i.e LHR at the end of the plan for 1.948 SMP/day; 2) value of CBR is 2.423% and E of 36.345 Psi; 3) functional quantities of pavement systems include (a) value of Po is 4.0; (B) valu of Pt is 1.5; and (c) value of Pf is 2.0; 4) value of R is 95% and S is 0.35; and 5) value of SN is 3 cm, and (c) the strength of road construction are 1) value of s is 1.065, 2) value of d is 5 deflections, and 3) value of FK is 0.47% and (2) the analysis of costs consistof (a) the total project cost Rp.10.142.160.500,00, (b) savings BOK (Vehicle Operating Costs) of the three dominant types of vehicles passing through Tanjung Kemuning Street, ie passenger cars, truck/bus medium, and truck/bus large amount Rp.953.814.502,55 covering fixed costs and variable costs Rp.878.980.000,00 of Rp.74.834.502,55, and (c) saving travel time of 0.6hours. This means that with the construction of feeder roads Kaur District-Bengkulu province,road users can save travel time for 0.6 hours compared to pre-project or equal to Rp.572.288.701,53; (2) evaluation of the economic viability include (a) the economic analysis, the value of BCR with an interest rate of 10% at 1,490, the interest rate of 12% amounting to 1,487, and the rate of 15% at 1,482. All the BCR value greater than 1, NPV at 10% interest rate for Rp.5.068.189.644,36, interest rates on 12% of Rp.4.570.421.018,57, and a 15% interest rate for Rp.4.451.192.644,17 , and the value of EIRR of 15.41% and (b) the sensitivity analysis obtained values BC(Benefit-Cost) nothing is worth (-).